Measles and Pregnancy: Immunity and Immunization—What Can Be Learned from Observing Complications during an Epidemic Year - Rosalia Ragusa; Armando Platania; Mario Cuccia; Gaetano Zappalà; Gabriele Giorgianni; Placido D’Agati; Maria Alessandra Bellia; Marina Marranzano (Journal of Pregnancy)
Measles is a highly contagious airborne disease. Unvaccinated pregnant women are not only at risk of infection but also at risk of severe pregnancy complications. As measles causes a dysregulation of the entire immune system, we describe immunological variations and how immune response mechanisms can lead to adverse pregnancy outcomes. We evaluated data during the measles outbreak reported in the province of Catania, Italy, from May 2017 to June 2018. We controlled hospital discharge records for patients admitted to hospital obstetric wards searching the measles diagnostic code. We have indicated the case as “confirmed” when the IgM was found to be positive with the ELISA method. We registered 843 cases of measles and 51% were females (430 cases). 24 patients between the ages of 17 and 40 had measles while they were pregnant. Adverse pregnancy outcomes included 2 spontaneous abortions, 1 therapeutic abortion, 1 foetal death, and 6 preterm deliveries. Respiratory complications were more prevalent in pregnant women (21%) than in nonpregnant women with measles (9%). 14 health care workers (1.7%) were infected with measles, and none of these had been previously vaccinated. Immune response mechanisms were associated with adverse pregnancy outcomes in women with measles. To reduce the rate of measles complications, gynaecologists should investigate vaccination history and antibody test results in all women of childbearing age. During a measles outbreak, gynaecologists and midwives should be active proponents of vaccination administration and counteract any vaccine hesitancy not only in patients but also among health care workers.